Considering the Effects of Upper Body, Lower Body, and Their Combination on Post-Activation Performance Enhancement of Bowling Velocity Among Amateur Cricket Players - Bhargav Sarmah; Nishanta Bordoloi; Pushpendra Narvariya; Rohit Kumar Thapa (Physical Education Theory and Methodology)
Objectives. This study aimed to investigate the effects of post-activation performance enhancement on bowling velocity among amateur cricket players using multiple interventions as conditioning activities focusing on the upper body, lower body, and a combination of both.